The lotus empire - Suri, Tasha (Suri, Tasha. Burning kingdoms, 2024)
"Malini has claimed her rightful throne as the empress of Parijatdvipa, just as the nameless gods prophesied. Now, in order to gain the support of the priesthood who remain loyal to the fallen emperor, she must consider a terrible bargain: Claim her throne and burn in order to seal her legacy-or find another willing to take her place on the pyre. Priya has survived the deathless waters and now their magic runs in her veins. But a mysterious yaksa with flowering eyes and a mouth of thorns lies beneath the waters. The yaksa promises protection for Ahiranya. But in exchange, she needs a sacrifice. And she's chosen Priya as the one to offer it. Two women once entwined by fate now stand against each other. But when an ancient enemy rises to threaten their world, Priya and Malini will find themselves fighting together once more - to prevent their kingdoms, and their futures, from burning to ash"--